Extraction and enrichment of flavonoid and evaluation of antioxidant activity of Passiflora foetida extract - Phan Thị Diễm, Trân; Trần Phương, Hà; Vũ, Thị Thanh Tâm; Tôn Thất, Hữu Đạt; Cường, Lê Cảnh Việt (Hue University Journal of Science: Natural Science, 2025)
Passiflora foetida L., commonly known as Lạc tiên in Vietnam, is a widely used medicinal plant in Vietnamese traditional medicine to treat diseases such as sedation, fever reduction, liver cooling, nervous breakdown, heart palpitations, and insomnia. In this study, the appropriate conditions for the extraction of P. foetida L. were determined as follows: 80% ethanol as the solvent, the solvent-to-material ratio of 10:1, the extraction temperature of 80 °C, the extraction time of 120 minutes, and the number of extractions 3 times. Activated charcoal was employed to remove chlorophyll before enriching flavonoids in the extract with Diaion HP20 resin. The enrichment process utilised 10% ethanol as the loading solvent with an extract-to-resin ratio of 16:30 (w/w). The elution with 70% ethanol increased the flavonoid content in the extract to 13.89%. Furthermore, the enriched extract exhibited strong antioxidant activity, with an IC50 value of 34.25 µg/mL.